2018
DOI: 10.1016/j.molimm.2018.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Critical steps for computational inference of the 3′-end of novel alleles of immunoglobulin heavy chain variable genes - illustrated by an allele of IGHV3-7

Abstract: Sequencing of immunoglobulin germline gene loci is a challenging process, e.g. due to their repetitiveness and complexity, hence limiting the insight in the germline gene repertoire of humans and other species. Through next generation sequencing technology, it is possible to generate immunoglobulin transcript data sets large enough to computationally infer the germline genes from which the transcripts originate. Multiple tools for such inference have been developed and they can be used for construction of indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…We managed to validate a number of novel alleles by targeted amplification of genomic DNA of the same individuals. In addition, we report the presence of G at position 318 instead of A in the gDNA sequence of IGHV3-7*02 , which supports the findings of previous studies 31, 32 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We managed to validate a number of novel alleles by targeted amplification of genomic DNA of the same individuals. In addition, we report the presence of G at position 318 instead of A in the gDNA sequence of IGHV3-7*02 , which supports the findings of previous studies 31, 32 .…”
Section: Discussionsupporting
confidence: 92%
“…Genomic validation of IGHV3-7*03_G144A revealed a further polymorphism in the intron. During validation of this allele, we also managed to amplify the genomic sequence of IGHV3-7*02 , which carried the previously reported polymorphism A318G 31 . This polymorphism was not inferred from the AIRR-seq data in our study, since the default parameters of the inference tools are set to detect polymorphisms up to position 312.…”
Section: Resultsmentioning
confidence: 99%
“…We cannot rule out the possibility that this analysis failed to identify SNVs in either the terminal 5′ or 3′ nucleotides of the IGHD sequences, though we believe this is unlikely. It has been shown that the inference process is often unable to accurately identify terminal nucleotides in adaptive immune receptor repertoire‐sequence (AIRR‐seq) data . By contrast, the antibody repertoire of the mouse is strongly shaped by joining at sequences of short homology and there may be strong evolutionary pressure maintaining, for example, the identity between the 3′ ends of the IGHD2 gene family and the 5′ ends of some IGHJ sequences, thereby preventing the development of variation in the terminal IGHD gene nucleotides.…”
Section: Discussionmentioning
confidence: 99%
“…Safonova and Pevzner [28] recently developed the IgScout algorithm for de novo inference of D genes using immunosequencing data. Unlike algorithms for de novo inference of V and J genes [23,24], it does not rely on alignments against closest germline genes that might lead to erroneous inferences [29,30]. Instead, IgScout uses the observation that the most abundant k-mers in CDR3s arise from D genes (a k-mer refers to a string of length k).…”
Section: Introductionmentioning
confidence: 99%